Kebijakan Pengelolaan Dana BOS (Upaya Meningkatkan Kualitas Pendidikan Madrasah Ibtidaiyah di Provinsi Kalimantan Barat) - Supriyanto (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper examines the policy of School Operational Assistance Fund (BOS) management as an effort to improve the quality of education in Elementary Madrasahs (MI) in West Kalimantan Province. The main focus is on the analysis of policy implementation, impacts on the quality of education, and challenges and solutions in managing these funds. This paper uses a qualitative method with a descriptive analysis approach, where the author collects data through document studies and in-depth interviews with related parties (madrasah principals, teachers, BOS fund managers, and officials at the Regional Office of the Ministry of Religious Affairs of West Kalimantan Province), and field observations in several state and private MIs. The collected data is analyzed using triangulation to gain a comprehensive understanding of the effectiveness of BOS Fund management. The results of the study show that BOS Funds make a significant contribution to improving the quality of MI education, especially in terms of facilities and infrastructure, teacher professional development, and learning activities. However, there are still several problems that need to be followed up with productive policies, such as limited human resource capacity and potential deviations from the use of BOS funds. Therefore, it is necessary to increase supervision, training, and utilization of technology to ensure more transparent and accountable management of BOS Funds to realize quality MI education in West Kalimantan.